Performance Appraisal of Seluma Districts Agricultural Extensionist with Fuzzy Simple Additive Weighting Method - Suranti, Dewi; Ikhsan, Mohamad (Scientific Journal of Informatics, 2017)
Measuring the performance of an agricultural extensionist is essential for future evaluation and monitoring. An appraisal of agricultural extensionist workers should be performed to determine the achievements achieved by each agricultural extensionist agent. For that according to Permentan 2013 every Agricultural organization is obliged to conduct agricultural extensionist performance appraisal. This study aims to measure the peformance of agricultural extensionist of Seluma Regency by using Fuzzy Simple Additive Weighting (FSAW) method because this method determines the weight value for each attribute, followed by a ranking process that will select the best alternative from a number. This study aims to apply Fuzzy Simple Additive Wighted in the assessment of agricultural extensionist performance in Seluma district and to know the performance of agricultural extensionist workers in organizing agricultural extensionist. The system built is expected to facilitate BP3K sukaraja in carrying out routine performance appraisal of extensionist worker who has been a constraint in carrying out the appraisal performance appraisal. This system can result in accurate assessment of the performance of extensionist workers in accordance with the programs and work plans that have been made and implemented by agricultural extensionist.